Highly dispersed Cu nanoparticles decorated on MOF-5: development of highly efficient noble metal-free electrocatalyst. Issue 2 (17th June 2021) - Parkash, Anand; Ali, Salamat; Arain, Adeel Mukhtar; Aziz, Shaheen
Abstract: Developing highly valuable electrocatalysts that can possess higher activity to replace conventional Pt catalysts for an oxygen reduction reaction (ORR) remains a major challenge. A cost-effective copper doped porous carbon (Cu-PC) has been synthesized here by carbonizing Cu that contains metal-organic framework (MOF)-5. Results show the Cu-PC exhibits ORR activity by following the four-electron route, and the number of electron transfers ( n ) is nearly 4. In addition, onset potential ( E o ), half-wave potential ( E 1/2 ), and limiting current density ( J L ) are nearly equal and far better than commercial Pt/C (20 wt.%). The Cu-PC-800 exhibits superior activity with E o 0.99 V and E 1/2 0.87 V compared to commercial Pt/C ( E o 0.94 V and E 1/2 0.83 V) as well as from several prepared catalysts. More importantly, the Cu-PC-800 displays superior stability in alkaline solution compared to Pt/C catalyst. These superior activities are attributed to the interaction of Cu nanoparticles with the support of porous carbon. The effects of carbonizing temperature and Cu doping on the ORR activity have been studied. The electrochemical tests showed that both metal doping and the temperature of pyrolysis could induce the electrocatalytic activity. The metal codoping and carbonizing approach will positively affect electrocatalyst efficiency and guide the development of new transition metal porous carbon ORR electrocatalysts.